Examining Online Indicators of Extremism among Violent and Non-Violent Right-Wing Extremists - Scrivens, Ryan (Terrorism and political violence, 2023)
Although there is an ongoing need for law enforcement and intelligence agencies to identify and assess the online activities of violent extremists prior to their engagement in violence offline, little is empirically known about their online posting patterns generally or differences in their online patterns compared to non-violent extremists who share similar ideological beliefs particularly. Even less is empirically known about how their online patterns compare to those who post in extremist spaces in general. This study addresses this gap through a content analysis of postings from a unique sample of violent and non-violent right-wing extremists as well as from a sample of postings within a sub-forum of the largest white supremacy web-forum, Stormfront. Here the existence of extremist ideologies, personal grievances, and violent extremist mobilization efforts were quantified within each of the three sample groups. Several notable differences in posting patterns were observed across samples, many of which may inform future risk factor frameworks used by law enforcement and intelligence agencies to identify credible threats online. This study concludes with a discussion of the implications of the analysis, its limitations, and avenues for future research.